Differences in the Development of Language and Social Independence in Children with Speech Delay and Sensorineural Hearing Loss based on the Age for Early Intervention and the Duration of Auditory-Verbal Therapy - Purwanti, Zamrotu Iva; Romdhoni, Achmad Chusnu; Suryawan, Ahmad; Purnami, Nyilo; Ariningtyas, Ninuk Dwi (Folia Medica Indonesiana, 2023)
Highlights : • This study explored the significance of auditory-verbal therapy as an early intervention for children with speech delay and sensorineural hearing loss, a topic that deserves further research in developing countries such as Indonesia. • The findings highlight the significance of age and therapy duration on the language development of children with speech delay and sensorineural hearing loss. Abstract Speech delay is primarily attributed to sensorineural hearing loss, which may significantly impact a child's language development and social independence. Consistent and periodic auditory-verbal therapy as an early intervention has the potential to positively influence language development, thereby fostering independence in children. The objective of the research was to examine the differences in the development of language and social independence among children who have speech delay and sensorineural hearing loss at the children's age for early intervention and with the duration of auditory-verbal therapy taken into consideration. The research employed an analytical-observational design with a cross-sectional approach and total sampling. The sample comprised 29 children who were undergoing the weekly routine of auditory-verbal therapy at Yayasan Aurica, Surabaya, Indonesia. The tool utilized in this study was the Pre-Screening Developmental Questionnaire. The data underwent bivariate analysis, specifically using the Chi-squared test with a significance level set at a p-value of <0.05. The language development analysis resulted in a p-value of 0.013 for the age variable and a p-value of 0.019 for the therapy duration variable. Meanwhile, the social independence analysis yielded a p-value of 0.229 for the age variable and a p-value of 0.111 for the therapy duration variable. In conclusion, the influence of age on early intervention had a significant difference from that of the duration of auditory-verbal therapy on the language development of children with speech delay and sensorineural hearing loss. Conversely, age and therapy duration did not exert any meaningful difference in terms of their influence on the children's social independence development.